Berberine Regulated miR150-5p to Inhibit P2X7 Receptor, EMMPRIN and MMP-9 Expression in oxLDL Induced Macrophages - Lu, Lin; Huang, Jianjian; Xue, Xia; Wang, Ting; Huang, Zhouqing; Li, Jianmin (Frontiers in Pharmacology, 2021)
Elevated extracellular matrix metalloproteinase inducer (EMMPRIN) and matrix metalloproteinase-9 (MMP-9) in oxidized low density lipoprotein (oxLDL)-induced macrophages leads to the progression of vulnerable plaques by degradation of the extracellular matrix. Our previous report showed that berberine regulates the expression of both EMMPRIN and MMP-9. In addition, P2X7 receptor (P2X7R) upregulation plays a crucial role in the development of atherosclerosis. However, it is unclear whether P2X7R regulates the expression of both EMMPRIN and MMP-9 in macrophages. In the present study, we investigated the impact of berberine on P2X7R expression and the regulation of P2X7R in the expression of EMMPRIN and MMP-9 in oxLDL-induced macrophages. We found that P2X7R expression was increased in oxLDL-induced macrophages in a dose-dependent manner, and A-438079 (a P2X7R inhibitor) treatment greatly reversed the upregulation of EMMPRIN and MMP-9 expression. Moreover, A-438079 significantly reduced oxLDL-induced AMP-activated protein kinase-α (AMPK-α) phosphorylation and reversed the activation of mitogen-activated protein kinase (MAPK), which in turn decreased the expression of EMMPRIN and MMP-9. These findings illustrate that P2X7R suppresses EMMPRIN and MMP-9 expression by inhibiting the AMPK-α/MAPK pathway in oxLDL-induced macrophages. Accordingly, exposure to berberine markedly decreased P2X7R expression and downregulated MMP-9 and EMMPRIN levels in oxLDL-induced macrophages, resulting in AMPK-α/MAPK (JNK, p38, and ERK) inactivation. Overall, these results indicate that berberine inhibits P2X7R-mediated EMMPRIN and MMP-9 expression by suppressing AMPK-α and MAPK signaling in oxLDL-induced macrophages.